Hubungan antara Locus Of Control dan Efektivitas Komunikasi antar Pribadi dengan Problem Focused Coping - Eko Sujadi; A Muri Yusuf; Marjohan Marjohan (Universitas Negeri Padang, 2016)
Problem focused coping need to be possessed by every individual. The purposes of this research were to described locus of control, the effectiveness of interpersonal communication, problem focused coping,the correlation between locus of control with problem focused coping, andthe correlationbetween the effectiveness of interpersonal communication with problem focused coping.This research was descriptive & correlation research by using quantitative approach. Data were collected through a Likert scale questionaire and locus of controlby using inventory Rotters Internal-External Locus of Control (I-E Scale), which was the validity and reliability has been tested. The data were analyzed by percentage technique and product moment correlation. The finding of research are:  1)locus of control were in the middle range between internal locus of control and external locus of control with an average as big as 11.46, 2) the general level of effectiveness of interpersonal communication is in high category, 3) the general level of problem focused coping is in high category, 4) there is correlation between locus of control withproblem focused coping, and 5) there is correlation betweeneffectiveness of interpersonal communicationwithproblem focused coping.